Perbandingan Konsep Orisinalitas Karya Cipta Ilustrasi Hasil AI Antara Indonesia dan Swedia - Naeli Rizqi Marhamah (Fakultas Hukum, Universitas Warmadewa, 2025)
Illustrations generated by artificial intelligence (AI), commonly referred to as Artificial Intelligence Generated Content (AIGC), have raised significant challenges in copyright law, particularly concerning originality, ownership, and enforcement. This study aims to analyze and compare the legal approaches of Indonesia and Sweden regarding the protection and enforcement of copyright for AI-generated illustrations. Employing a normative juridical-comparative method, the findings reveal that AI-generated illustrations do not qualify for copyright protection in either Indonesia or Sweden due to the inability of AI to satisfy the originality principle, which requires human creativity, and its incapacity to be recognized as a legal subject. In Indonesia, the Copyright Law (Law No. 28 of 2014) does not explicitly regulate works produced by AI. In contrast, Sweden has made significant progress by harmonizing its domestic regulations with the European Union’s AI Act, set to be fully implemented by 2026. As part of enforcement efforts, the national research body “AI Sweden” plays a pivotal role in exploring mechanisms for enforcing copyright over AI-generated illustrations. This study recommends revising Indonesia's Copyright Law to ensure relevant legal protection and develop effective enforcement mechanisms for AI-generated illustrations, aligning with technological advancements and the needs of the creative industries.